AGRONOMIC PERFORMANCE OF LOWLAND RICE (ORYZA SATIVA L.) VARIETIES AS AFFECTED BY DIFFERENT WATER REGIMES - Cagasan, Ulysses A; Cagasan, Christian Ulysses G (Journal of Agriculture and Technology Management, 2021)
It is crucial to know the crop's physiological and morphological characteristics to provide specific cultural management practices. This study aimed to determine the growth and yield performance of the three lowland rice varieties with different morphological maturity grown in different water regimes and identify the maturity period of rice varieties that would give the optimum yield. The experiment was laid out in a complete randomized design (CRD) with three replications. Each replication was subdivided into three treatment pots (20 cm x 25 cm x 23 cm size pail) filled with pulverized clay loam soil. Each container was arranged at a 50 cm distance to facilitate management and data gathering. Water Regimes as the main plot (MP); MP 1 - AWD, MP 2 -Flooded.while, Different morphological maturity of rice varieties as the sub plot; T 1 – NSIC Rc10 (Early maturing variety-85 days), T 2 – NSIC Rc216 (Medium maturing variety-105 days), and T 3 – NSIC Rc222 (Late maturing variety-120 days). Treatment NSIC Rc10 (T 1 ) had a shorter plant height (cm) with lesser number of tillers per hill than NSIC Rc216 (T 2 ) and NSIC Rc222 (T 3 ). However, (T 1 ) early maturing rice varieties produced a greater number of filled grains per panicle and heaviest weight of 1000 grains; thus, resulted in higher grain yield at 26 g than T 2 and T 3 at 20 and 21 g. Likewise, T 2 and T 3 had a comparable number of filled grains and weight of 1000 grains which resulted in a significantly similar yield between these two varieties.